Verbatim Record of the Ninth Meeting (Closed) - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations Special Committee on the Problem of Hungary The committee asked Béla Király in connection with his earlier statement: his military career, and the charges against him which led to his imprisonment. Further questions related to the negotiations with the Soviet military authorities, the capture of the Hungarian delegation led by Maléter, the process of appointing the Prime Minister of Hungary, the events in front of the Radio building, and the role of Imre Nagy at the beginning of the revolution. The committee examined in detail the question of who requested that Soviet troops enter the country.